Training on the Importance of Making Financial Reports for MSME in Ujung Rambe Village - Novien Rialdy; Sultan Farid Fauzi Hasibuan (PT FORMOSA CENDEKIA GLOBAL, 2022)
This community service is carried out with the aim of being able to assist the community in financial reporting mechanisms, especially for MSMEs in Ujung Rambe Village. Financial reports serve as a tool for analyzing financial performance which can provide information about financial position so that it can be used as a basis for making decisions. MSMEs are productive businesses owned by individuals or business entities that meet the criteria of being a micro business. Financial reports are a form of MSME accountability. Even though in villages, village communities cannot be left behind regarding financial reports, financial reports are made to present information regarding the performance of MSMEs. The result of this service is to increase understanding of the importance of MSME financial reports. The method in this service uses descriptive because the service obtained is based on the results of interviews with village heads, village officials and the community. The media used is in the form of documents. The importance of financial reports to MSMEs with the hope that MSMEs in Ujung Rambe Village are able to know the performance of the business being run and can be used for decision making. By holding student services to Ujung Rambe Village, it can overcome problems that do not yet know about financial reports. Hopefully with this training the problems in Ujung Rambe Village can be overcome.